Development of a Cleavable Biotin‐Drug Conjugate Hydrogelator for the Controlled and Dual Delivery of Anticancer Drugs. Issue 13 (7th April 2021) - Das, Soumi; Kumar Thakur, Krishan; Kunnumakkara, Ajaikumar B.; Kundu, Lal Mohan
Abstract: Hydrogels based drug delivery has found extensive application recently. In most of the cases, polymers and peptide based hydrogels were used in drug delivery. In this report, we have developed a hydrogelator containing an anti‐tumor agent 5‐Fluorouracil (5‐Fu). The design comprised of a photo‐responsive prodrug of 5‐Fu covalently conjugated to an essential nutrient, biotin (vitamin B7), providing the hydrogelator high biocompatibility. The synthesized molecule formed hydrogel at pH 7. The hydrogel also can effectively entrap another water‐soluble chemotherapeutic agent doxorubicin hydrochloride (DOX). The release of 5‐Fu was observed in a light dependent manner whereas sustained release of DOX was recorded from the hydrogel. The controlled and sustained release of both the drugs were monitored by UV‐Vis, fluorescence spectroscopy and 1 H NMR study. Such 5‐Fu‐biotin gel could be useful as a dual drug carrier for effective delivery of two hydrophilic antitumor agents simultaneously. Abstract : A strategy of dual drug delivery via a biotin‐based hydrogel is demonstrated. Biotin (vitamin B7), an essential nutrient that also binds to an overexpressed receptor in specific cancer cells, was conjugated to a prodrug of 5‐Fluorouracil through a light‐cleavable linker. The hydrogel was also capable of loading another hydrophilic chemotherapeutic drug, doxorubicin hydrochloride. DOX was released from the hydrogel in a diffusion‐controlled manner. The developed hydrogel could have applicability as a dual drug delivery vehicle for anticancer therapy.